Corn Yield Response to Plant Populations - D. E. Shoup; Eric Adee; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2016)
Corn hybrid development with a focus on drought tolerance has emerged in recent years, and producers have questions about their yield performance across a range of plant populations. A three-year study was conducted to determine the yield of corn hybrids across several plant populations. Corn hybrids responded differently across three different yield environments in 2013, 2014, and 2015. In 2013, a lower yield environment occurred. The hybrid with drought tolerance had the greatest yield of 95 bu/a at a plant population of 21,500 plants/a, whereas the non-drought tolerant hybrid’s greatest yield was 90 bu/a at a plant population of 13,500 plants/a. In 2014, the yield environment was the greatest in the three-year study. The hybrid with drought tolerance had the greatest yield of 174 bu/a at the greatest plant population of 35,500 plants/a, and the non-drought tolerant hybrid’s greatest yield was 169 bu/a at a plant population of 29,500 plant/a. In 2015, overall corn yield was moderate compared to 2013 and 2014. The hybrid with drought tolerance once again had the greatest corn yield at 135 bu/a at the 29,500 plant/a population.
Keywords: Corn; plant populations; drought tolerance